Carbon Emission Disclosure in Indonesian Consumer Goods Manufacturing Companies During Covid-19 Pandemic - Fransisco Pandapotan (FEB - Universitas Lampung, 2023)
Disclosing carbon emission in the annual reports will assist the stakeholders to assess the company’s role in reducing the greenhouses gases and investors to decide their investments. Therefore, the objective of this research is to test the effect of environmental performance, international certification, board independence, and board female on carbon emission disclosure during Covid-19. The population used in this research is all consumer goods manufacturing companies listed in Indonesia Stock Exchange period 2020-2021. Purposive sampling is used in this research with some criteria made. The analysis method is multiple linear regression with SPSS 22 as a tool. The results of this research prove that environmental performance and board independence have significant positive effects on carbon emission disclosure whereas international certification and board female do not have any significant effects on carbon emission disclosure.